Colonic Infection by Bilophila wadsworthia in Pigs - McOrist, Alexandra L. (American Society for Microbiology, 2001)
Bilophila wadsworthia is a common inhabitant of the human colon and has been associated with appendicitis and other local sites of inflammation in humans. Challenge-exposure or prevalence studies in laboratory and other animals have not been reported. B. wadsworthia is closely related phylogenetically to Desulfovibrio sp. and Lawsonia intracellularis, which are considered colon pathogens. We developed a PCR specific for B. wadsworthia DNA. Samples of bacterial DNA extracted from the feces of pigs on six farms in Australia and four farms in Venezuela were examined. Specific DNA of B. wadsworthia was detected in the feces of 58 of 161 Australian and 2 of 45 Venezuelan pigs, results comprising 100% of the neonatal pigs, 15% of the weaned grower pigs, and 27% of the adult sows tested. Single-stranded conformational polymorphism analysis of PCR product DNA derived from pigs or from known human strains showed an identical pattern. Histologic examination of the intestines of weaned B. wadsworthia-positive pigs found no or minor specific lesions in the small and large intestines, respectively. B. wadsworthia is apparently a common infection in neonatal pigs, but its prevalence decreases after weaning. The possible role of B. wadsworthia as an infection in animals and in human colons requires further study.